PERLINDUNGAN KONSUMEN ATAS KERUGIAN PELAYANAN DAN KENAIKAN BIAYA INDIHOME DI KOTA PADANG - Vony Febryan (UNES Law Review, 2020)
The problems discussed:How are consumers protection for service losses and increased indihome costs in padang city? How are Dispute resolution of consumer in service losses and increased of indihome costs?This research is Descriptive analytical, normative juridical and empirical juridical approach conducted in Padang city By using interview consumers, and manager of customer care (PT) Telecommunications Indonesia Regional of Padang. The results of this researchConsumer protection for the loss of service and an increase in the cost of Indihome in the city of Padang that the consumer has not fully obtained legal protection, because PT. Telkom only cancel Internet content Catchplay service To prevent future charges from appearing, An Indihome service fee increases that the charge is still charged to the consumer. In the absence of compensation from PT. Telkom, consumers are Highly harmed.Dispute resolution of consumer Loss of service and increase of indihome costs is the consumer only signed a statement letter containing the release of PT. Telkom City of Padang demands,PT.TELKOM does not conduct deliberations in accordance with the provisions Indihome Contract subscription regarding the settlement of disputes between PT. Kota Padang Telkom with the customer must be resolved by means of deliberation.